INTRODUCING THE POSITION OF NUMBERS THROUGH GUESS MY NUMBER GAME - Fajri, Sakinah Nurul (journal of RESIDU, 2018)
This paper discusses an activity which is a part of design research in line with Realistic Mathematics Education (RME). The aim of the study is to design an instructional activity that can introduce the idea of the position of numbers on closed number line. This paper describes the use of guess my number game to introduce the position of numbers on closed number line to second grades pupils in Indonesia age ranged from 8 to 9 year. The episodes of classroom discussion were analyzed to see how the design works. The analysis focuses on the role of the game in emerging the idea of the position of numbers. The observation provides the information of classroom norms that allows pupils to attain mathematical idea. The analysis reveals that the idea of the position of numbers emerged when pupils engaged in the game.